PKM Pendampingan Guru di Sekolah Dasar Kabupaten Malang Dalam Pengembangan Media Pembelajaran - Zaqqi Ubaidillah; Chairul Huda Al Husna; Deviansyah Vanda Alviana; Ariny Ilma Sakina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
There are various problems for teachers in learning, namely, those who are still very traditional who cannot follow the rhythm during a pandemic which requires going online. Therefore, we provide a solution, we provide training for teachers to have additional IT skills, so that they can be utilized in the teaching and learning process and as learning media. This service method is carried out using various approaches, namely, workshops and providing videos. The importance of using IT in the learning process is to make it easier for teachers and also students' understanding. IT cannot be separated from children's lives today. The suggestion from the results of this service is that teachers must always keep up with the times. This is because each generation has a different pace and way of learning